Applying quality function deployment in the development of a finger based hand exerciser for computer application / Muhamad Zaid Jamal - Jamal, Muhamad Zaid (2017)
Conventional product conceptual design is an abstract and creative process but Quality Function Deployment (QFD) is the means for a systematic approach. QFD makes developments be based on customers and the QFD process assures their satisfaction throughout. On a first objective of this research QFD is adopted as a strategy to develop a new hand exerciser of the interactive kind and for the purpose to be able to further contribute in its process domain. QFD helped to acquire knowledge about the product being developed and manage the product development process which in turn product uncertainty and a chaotic product development process is expected or without best practices. Additionally to QFD as known popularly, a process framework is adopted called the Blitz QFD which refines data collection and analysis processes. For a second objective of the research, the interactive hand exerciser is proved technical viable after all request or new knowledge about it is retrieved during objective one. Based on those, this research produced a prototype and have detailed on development tools and solutions. Prototype designs can become stepping stones for better ones in the future for any product developer. On a third objective of the research, initially there was least evident as for it to be desirable or will it be an effective one. Setting out to prove so, as it was a positive indication by the literature, in surveys, none met rejected the idea but provided suggestions for product improvement. In agreement tests, survey population sports student agreed the device would be an interesting hand exerciser or a rehabilitation tool besides all agreed the game is interesting. They need not be realizing it is good exercise but just have fun. For true health benefits, expert physiotherapists were asked for their review and they confirmed it ought to be useful. Some corrections were voiced but for detailed implication collaboration-ship with the experts is a must in future research and development iterations that coming from the engineering department. Though, to make clear on contributions, this research is a QFD case study for a methodological contribution. As an artifact contribution, it entails on development tools and designs for the interactive exerciser. For an empirical contribution, it provides the support for an interactive hand exerciser to be further developed. As a survey contribution, the literature is synthesized for the state of art in both gist; QFD methodology and an interactive hand exerciser.